English Students' Perceptions on The Use of Online Learning Platforms during The COVID-19 Pandemic - Arina Hafadhotul Husna (JEE (Journal of English Education), 2022)
This study explores English students’ perceptions of the use of online learning platforms during the COVID-19 pandemic. It focuses on students’ participation, accessibility, material & assignment delivery, and the preferences of online learning platforms. The researcher conducted a qualitative study by using the survey design method. It used a questionnaire as the instrument; it was then distributed and collected through Google form. There were open-ended questions that required a free text response which was used to gain the students’ perception regarding online learning implementation, while close-ended questions were used to obtain the percentage of the analyzed topic. The received responses were calculated, analyzed, and described narratively. The respondents were 87 students of three departments of STIKES Cendekia Utama Kudus in the odd semester. The result presents that students showed a positive attitude during English online learning. Since they had an unstable connection, they showed their positive effort. Their response to the material & assignment delivered by their lecturer was positive. However, the students had many obstacles during the process; accessibility still becomes their main problem. Unstable Signal strength, full smartphone storage, and given assignments need to be considering too. They need extra time to submit their assignments because of the connection. Since their connection is limited and unstable, WhatsApp, Google Meet and YouTube studio became their most favorite platform. It was quota-friendly, had a stable connection, and was flexible. They can re-play/re-read their material wherever and whenever they need it.